Does DPP-IV Inhibition Offer New Avenues for Therapeutic Intervention in Malignant Disease? - Busek, Petr; Duke-Cohan, Jonathan S; Sedo, Aleksi (Cancers, 2022)
Dipeptidyl peptidase IV (DPP-IV, CD26) is frequently dysregulated in cancer and plays an important role in regulating multiple bioactive peptides with the potential to influence cancer progression and the recruitment of immune cells. Therefore, it represents a potential contributing factor to cancer pathogenesis and an attractive therapeutic target. Specific DPP-IV inhibitors (gliptins) are currently used in patients with type 2 diabetes mellitus to promote insulin secretion by prolonging the activity of the incretins glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP). Nevertheless, the modulation of the bioavailability and function of other DPP-IV substrates, including chemokines, raises the possibility that the use of these orally administered drugs with favorable side-effect profiles might be extended beyond the treatment of hyperglycemia. In this review, we critically examine the possible utilization of DPP-IV inhibition in cancer prevention and various aspects of cancer treatment and discuss the potential perils associated with the inhibition of DPP-IV in cancer. The current literature is summarized regarding the possible chemopreventive and cytotoxic effects of gliptins and their potential utility in modulating the anti-tumor immune response, enhancing hematopoietic stem cell transplantation, preventing acute graft-versus-host disease, and alleviating the side-effects of conventional anti-tumor treatments.
Keywords: cancer; chemokine; drug repurposing; stromal cell-derived factor; immune response; tumor microenvironment; gliptin; stem cells